2014
DOI: 10.1136/tobaccocontrol-2014-051765
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of brand switching among adult smokers in the USA, 2006–2011: findings from the ITC US surveys

Abstract: Background Recent studies have suggested that about 1 in 5 smokers report switching brands per year. However, these studies only report switching between brands. The current study estimated the rates of switching both within and between brand families and examining factors associated with brand and brand style switching. Methods Data for this analysis are from the International Tobacco Control 2006–2011 US adult smoker cohort survey waves 5–8 (N=3248). A switch between brands was defined as reporting two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The reported usual sub-brand style smoked was categorized as "full flavor/regular," "light," or "ultralight" based on how the sub-brand style was labeled prior to the descriptor ban or on its current color coding, with those that could not be classified because of insufficient information coded as "other." Strength coding was based on Cornelius et al 31 and guided by our US investigators. For those without a usual brand and variant, last purchase brand and variant was used.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The reported usual sub-brand style smoked was categorized as "full flavor/regular," "light," or "ultralight" based on how the sub-brand style was labeled prior to the descriptor ban or on its current color coding, with those that could not be classified because of insufficient information coded as "other." Strength coding was based on Cornelius et al 31 and guided by our US investigators. For those without a usual brand and variant, last purchase brand and variant was used.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Although higher prices motivate some to quit, it is common for other smokers to find ways to reduce their cost of smoking and thus minimize the effect of a cigarette price increase [ 5 ]. There is an established body of literature that has detailed the price-minimizing behaviors of smokers including buying cheaper brands [ 3 , 6 , 7 ], buying cigarettes from low-tax or untaxed sources [ 7 , 8 ], using loose tobacco to roll their own cigarettes [ 7 , 9 , 10 ], using coupons and other discounts [ 4 , 11 ], buying different quantities to save money [ 5 , 7 , 10 , 12 ], and finding less expensive places to buy cigarettes [ 3 , 12 ]. A much smaller body of literature explores reducing the number of cigarettes smoked to save money [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of taxes on price-minimizing behaviors is largely based on cross-sectional population-based survey data [ 4 , 7 , 13 ]. Other types of studies such as longitudinal cohort studies have been limited to exploring the incidence of specific price-minimizing behaviors such as discount cigarette use [ 14 ] and brand switching [ 11 ], as well as the impact of price-minimizing behavior on subsequent smoking behavior [ 10 ]. Despite a call for qualitative exploration of price-minimizing behavior [ 6 ], the authors are aware of only one such study, which focuses on low-income smokers’ experiences of financial deprivation and smoking [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, NATS questions assessed the most recent cigarette brand purchase and thus may not necessarily reflect smokers overall purchasing behaviors, who may switch between generic and premium brands depending on the discounts offered by manufactures. 13,20 Since smokers’ self-reported use of price-related discounts in the 2009–2010 NATS reflects only direct-to-consumer discounts from the industry, the discount measure in the analysis does not include tobacco industry’s promotional allowances directly paid to cigarette retailers or wholesalers. Finally, the NATS is a cross-sectional survey; therefore, causal or temporal relationships cannot be established.…”
Section: Discussionmentioning
confidence: 99%
“…1113 As a result, a large proportion of US adult smokers (18%–49%) today have used multipack discounts, rebates, and coupons during purchases to reduce the costs of cigarettes, whereas another increasing fraction of US adult smokers (10%–34%) have used generic cigarette brands. 7,1220 The use of these strategies may mitigate the public health impacts of raising unit price of cigarettes, as studies have shown that smokers who used these pricing strategies are less likely to make quit attempts and to succeed in quitting in the future. 7,21,22 …”
mentioning
confidence: 99%